Efektifitas Konseling kepada Suami dalam Pengambilan Keputusan Menggunakan Metode Kontrasepsi Jangka Panjang - Andi Masnilawati; Akbar Asfar (FORIKES, 2023)
The results of previous research show that one of the factors associated with choosing a long-term contraceptive method is a lack of support from the husband. The aim of this research was to determine the influence of counseling for husbands in making decisions about selecting long-term contraceptive methods. This research implemented a one group pretest posttest design, which was carried out in the working area of the Kassi Kassi Community Health Center, Makassar City from September to December 2022. The subjects of this research were husbands of couples of childbearing age who were selected using a purposive sampling technique based on inclusion criteria. Decision making by husbands was measured through filling out questionnaires. Comparison of decision making between before and after counseling was analyzed using the Wilcoxon test. The results of the analysis showed that 65.37% of husbands chose long-term contraceptive methods after being given counseling (p=0.000). It was concluded that providing counseling to husbands was effective in supporting decision making in selecting long-term contraceptive methods.Keywords: long-term contraceptive method; counseling; husband's support ABSTRAK Hasil penelitian terdahulu menunjukkan bahwa salah satu faktor yang berhubungan dengan pemilihan metode kontrasepsi jangka panjang adalah kurangnya dukungan dari suami. Tujuan penelitian ini adalah untuk mengetahui pengaruh konseling kepada suami dalam pengambilan keputusan pemilihan metode kontrasepsi jangka panjang. Penelitian ini menerapkan rancangan one group pretest posttest, yang dilaksanakan di wilayah kerja Puskesmas Kassi Kassi Kota Makassar pada bulan September sampai Desember 2022. Subjek penelitian ini adalah suami pasangan usia subur yang dipilih dengan teknik purposive sampling berdasarkan kriteria inklusi. Pengambilan keputusan oleh suami diukur melalui pengisian kuesioner. Perbandingan pengambilan keputusan antara sebelum dan sesudah konseling dianalisis dengan uji Wilcoxon. Hasil analisis menunjukkan bahwa 65,37% suami memilih metode kontrasepsi jangka panjang setelah diberikan konseling (p = 0,000). Disimpulkan bahwa pemberian konseling kepada suami efektif untuk mendukung pengambilan keputusan pemilihan metode kontrasepsi jangka panjang.Kata kunci: metode kontrasepsi jangka panjang; konseling; dukungan suami